Arabic Linguistics And Phonetics* An Introduction To The Neo-khalilian Theory - Abderrahmane Hadj Saleh (Al-Lisaniyyat)
The starting point of the Neo-Khalilian theory is the discovery, for the most ancient grammarians (8th century), of an original conception that we do not find in the works of the arab grammarians who came after them only in a distorted form (except some cases). These ancient grammarians‚ and more particularly al-Ḫalil lbn Aḥmad (8th century), have underlined the most important function of language, i.e communication. However, they did not adopt it as their exclusive principle in the explanation of the linguistic phenomena. Thus, they have clearly separated what belongs to the communicationnal from what is related to the internal structure of language. The linguistic theory developed by these ancient researchers has been first analysed for many long years, then reformulated within a logico-mathematical framework and is actually systematically being exploited in several fields at the level of`our Center. The main concepts of the Neo-Khalilian theory: l. The notion of open corpus: Similarly to those of the physician or biologist, the data colleted by the linguist need to be validated thanks to their verifiable characteristic. 2. The distinction between the grammatical structure and the code, from one hand, and their use within the utterance from the other hand. *-This work was published in «Applied Arabic Linguistics and Signal and Information Processing«. Hemisphere. P.C., New York,1987, pp. 3-22. 3. The notion of structure in this theory goes beyond that of the post-saussurian structuralism: structure here is the result of the synthesis of the class and order. 4. Language units are not necessarily segments (or marginally accents). There is abstract denoters which have the same importance as the segmental or accentual denoters. Example: the nominal or verbal element`s pattern and root: each denotes a meaning in itself: the synthesis of the two denoters gives a segment whose meaning results also from the synthesis of the two abstract meanings (and not from their mixture or juxta-position). This being the result of the systematic application of the qiyās. Thus, the syntagmatic axis is thus abstract (not to be confused with the verbal chain) because: 1˚ it includes empty positions. 2˚ the order of the elements that constitute it is not necessarily that of the verbal chain. It is precisely, these two characteristics that distinguish this analysis from the Harissian one. 5. From another side, the transformations that constitute here the progressive passages from one sequence to other more complex ones according to very precise rules (additions, with or without exclusive alternation, combinations according to some patterns, position’s change, etc.) generate themselves the language items as opposed to generative grammar (1957 and 1965) where the generation of items is related to a first system which is only a simple axiomatisation of the I.C analysis.